A reconfigurable dual‐beam planar antenna with beam switching capability. Issue 12 (22nd September 2017) - Lalithamma, Snehalatha; Pathak, Nagendra P.; Manhas, S. K.
Abstract: A novel dual‐beam planar antenna with pattern reconfigurable feature is presented in this article. The proposed design uses four antenna elements, two of which are connected at a time to provide dual‐beam reconfigurability. Four PIN diodes are employed to achieve switching of the dual‐beam in four directions. A prototype of the antenna is fabricated on FR4 substrate with a single coaxial feed and the results are validated by measurement.